A Qualitative Research on the Winter Sports Body-Building Activities of Chinese Residents from the Perspective of Social Stratification - Wen Wang; Yong Wang * (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Social stratum differences lay behind the winter sports body-building activities of Chinese residents. Guided by social stratification theory, this paper takes heterogeneity research as the paradigm, and carries out in-depth interviews to explore the winter sports body-building behaviors and concepts of Chinese citizens in three classes, namely, middle class (white collar), working class (blue collar), and unemployed (jobless) class. In addition, the authors explored the correlation of participation and experience of each class with economy, education, and society dimensions of snow sports culture. This paper holds that: a. Difference in economic conditions determine the level, scope, and degree of the participation of winter sports; b. The improvement of education level accelerates the socialization progress of participants, but it also increases the differentiation of individual participation and intensifies social stratification; c. The bidding and holding of Beijing Winter Olympics greatly promotes the development of winter sports in China, and forms a feature of “middle-class consumers”, while the consumption of the working class and unemployed (jobless) residents is more "rational". The paradigm of social stratification and heterogeneity research helps relevant researchers to break away from the narrow perspective of finding the individual-level causality behind winter sports body-building, laying the basis for social, and sports researchers to recognize and understand the unequal social structure of winter sports participation.